Motion in musical sound : the role of music performer bodily gesture in creating expressive sounding music - Allingham, Emma (2018)
The way that musicians move when they perform is closely linked with their communicative intent and artistic interpretation of the music. While research has shown that musicians’ bodily gesture conveys visually expressive information, no previous research has asked if these gestures are important to the musicians’ internal process of making the music sound expressive. As musicians often perform in situations when they cannot be seen, this question is relevant to issues of performance practice and pedagogy. This study investigated the importance of musicians’ use of expressive or ancillary gesture in the process of creating expressive sounding music. Four violinists were instructed to play unaccompanied melodies (intended to conveysad, happy, tender and scary emotions) under two movement conditions: visually expressive and immobile, while their performances were recorded through audio, and motion capture technology. The resulting audio performances were presented to listeners in a perceptual experiment in which listeners were asked to judge the overall expressivity of each performance, and the emotion conveyed by the music.It was hypothesised that: 1) melodies would be perceived as conveying the intended emotions, 2) there would be an effect of performance condition on expressivity ratings, and 3) performers would move more in the visually expressive condition than in the immobile condition. H1 was supported for six of the eight melodies, showing that those six melodies are suitable for future use in music and emotion research. H2 was supported for the two sad melodies and one happy melody, but was not supported for the other melodies, indicating that use of body movement can affect a performer’s expressivity through sound, but the effect may be influenced by various factors. H3 was supported for all performers, showing that the movement conditions used here were successful in manipulating performers’ body movement. In addition, exploring the descriptive statistics of the motion capture data also showed some interesting trends and differences in movement characteristics among the performers. Implications and limitations are discussed.